2003
DOI: 10.1080/0309190031000111380
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of heart rate variability from short-term recordings during five manoeuvres in normal subjects

Abstract: In healthy individuals, the temporal and spectral measurements of the heart rate variability from short-term records are stable in a five day period for the manoeuvres studied. Central frequencies of the spectral components might be used as indexes of the autonomic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 20 publications
2
19
1
1
Order By: Relevance
“…In one small study, significantly reduced intraCVs were found for LF and HF power for paced breathing (12 breaths/min) compared with spontaneous breathing [19]. However, in that study, indices were not logtransformed, which is surprising in light of the commonly described skewed distribution of HRV indices [22,33,38]. By definition, skewed data results in incorrect and falsely high S.D., which consequently overestimates the variation of the measurements.…”
Section: Hrv Indexmentioning
confidence: 80%
“…In one small study, significantly reduced intraCVs were found for LF and HF power for paced breathing (12 breaths/min) compared with spontaneous breathing [19]. However, in that study, indices were not logtransformed, which is surprising in light of the commonly described skewed distribution of HRV indices [22,33,38]. By definition, skewed data results in incorrect and falsely high S.D., which consequently overestimates the variation of the measurements.…”
Section: Hrv Indexmentioning
confidence: 80%
“…In general, the objective of previous works has been to assess the reproducibility of a subset of the HRV metrics used to study a specific patient population or condition of interest. These studies include research on the shortand long-term reproducibility of autonomic measures in supine and standing positions [31], reproducibility of HRV responses to graded lower body negative pressure [20,34], reliability of short-term HRV measures during exercise [3,28,30,62], reproducibility of measures of cardiovascular autonomic nervous function in middle age and elderly subjects [23], reproducibility of frequency domain HRV metrics before and after a standardized meal [18], HRV analysis reproducibility in the chronic phase of myocardial infarction [5], reproducibility of HRV from short-term recording during manoeuvres in normal subjects [9], stability of short recordings in time [54] and reproducibility of HRV metrics obtained from short-term sampling records [21,37]. In addition to the reproducibility of 24 h and 5 min records, assessing the reproducibility of HRV metrics calculated from very short records has significant practical importance [25], since it is not always possible to obtain 5 min records due to instrumentation constraints or study design [17].…”
Section: Resultsmentioning
confidence: 99%
“…Other researchers indicated that the ICC was suitable for verifying reproducibility because it can measure the association strength among repetitions (Carrasco et al, 2003;Reland et al, 2005). Reproducibility was considered to be "good" if ICC ranged from 0.61 to 0.81 and "almost perfect" if it exceeded 0.81 (Landis et al, 1977).…”
Section: Discussionmentioning
confidence: 99%